Limited duration of complete remission on ruxolitinib in myeloid neoplasms with PCM1-JAK2 and BCR-JAK2 fusion genes - Schwaab, Juliana; Metzgeroth, Georgia; Naumann, Nicole; Jawhar, Mohamad; Fabarius, Alice; Hofmann, Wolf-Karsten; Reiter, Andreas (Annals of hematology, 2014)
Rearrangements of chromosome band 9p24 are known to be associated with JAK2 fusion genes, e.g., t(8;9)(p22;p24) with a PCM1-JAK2 and t(9;22)(p24;q11) with a BCR-JAK2 fusion gene, respectively. In association with myeloid neoplasms, the clinical course is aggressive, and in absence of effective conventional treatment options, long-term remission is usually only observed after allogeneic stem cell transplantation (ASCT). With the discovery of inhibitors of the JAK2 tyrosine kinase and based on encouraging in vitro and in vivo data, we treated two male patients with myeloid neoplasms and a PCM1-JAK2 or a BCR-JAK2 fusion gene, respectively, with the JAK1/JAK2 inhibitor ruxolitinib. After 12 months of treatment, both patients achieved a complete clinical, hematologic, and cytogenetic response. Non-hematologic toxicity was only grade 1 while no hematologic toxicity was observed. However, remission in both patients was only short-term, with relapse occurring after 18 and 24 months, respectively, making ASCT indispensable in both cases. This data highlight (1) the ongoing importance of cytogenetic analysis for the diagnostic work-up of myeloid neoplasms as it may guide targeted therapy and (2) remission under ruxolitinib may only be short-termed in JAK2 fusion genes but it may be an important bridging therapy prior to ASCT.